Systems Thinking in Science Education: A Bibliometric Study over the Past Decade - Haryanto, Haryanto; Anwar, Sjaeful; Solihat, Rini; Habibaturrahmah, Zuana; Azzahra, Waliyyatu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to explore the publication trends in systems thinking within science education from 2014 to 2023, utilizing VOSviewer, Excel, and Biblioshiny for bibliometric analysis, to better understand how systems thinking is integrated into educational practices and its impact on managing complex systems. Analyzing 328 of 880 documents from the Scopus database, results show a gradual increase in publications, with leading journals including Sustainability Switzerland and the Journal of Chemical Education. The United States leads in research output, followed by China and Malaysia. The University of Colorado Boulder and Harvard Medical School are the most productive affiliations. Prominent authors include Yehudit Judy Dori and Jed D. Gonzalo. The most cited document by Grover et al. with 251 citations. Research trends highlight popular topics such as students, education, curriculum, learning, and teaching. However, gaps remain in connecting systems thinking with emerging fields like artificial intelligence, problem-based learning, problem-solving, decision-making, and STEM. These findings guide future research, resource allocation, and strategy formulation to enhance systems thinking in education. Further research using diverse data sources and methodologies is recommended to bridge gaps and improve the application of systems thinking principles.Keywords: bibliometric analysis, systems thinking, science education